#Selfies With a Mask On: Comparing Self-Presentation of Athletes From the U.S. and China in the 2020 Tokyo Olympics. (April 2023) - Xu, Qingru; Guo, Sitong; Kim, Eunhui
The purpose of this study is to explore Chinese and U.S. athlete self-presentation in the 2020 Tokyo Olympics. By examining 1200 photographs posted by Olympians on social media, this study finds that (a) male athletes feature themselves in more revealing clothes than female athletes, (b) Chinese athletes actively show more nationalistic notions compared to their U.S. counterparts, and (c) U.S. female athletes are involved in more subordinating behaviors than Chinese female athletes. This study underlines how the intersection of gender, nationalism, and culture influences athlete social media self-presentation in the global pandemic context. Possible explanations and implications are discussed.